Evaluation of a multimodal analgesic regimen on outcomes following laparoscopic living donor nephrectomy. Issue 8 (19th April 2021) - Marti, Kristen; Rochon, Caroline; O'Sullivan, David M.; Ye, Xiaoyi; Ebcioglu, Zeynep; Kainkaryam, Pranjali P.; Kuzaro, Hillary; Morgan, Glyn; Serrano, Oscar K.; Singh, Joseph; Tremaglio, Joseph; Kutzler, Heather L.
Abstract: Postoperative pain is a significant source of morbidity in patients undergoing living donor nephrectomy (LDN) and a deterrent for candidates. We implemented a standardized multimodal analgesic regimen, which consists of pharmacist‐led pre‐procedure pain management education, a combination transversus abdominis plane and rectus sheath block performed by the regional anesthesia team, scheduled acetaminophen and gabapentin, and as‐needed opioids. This single‐center retrospective study evaluated outcomes between patients undergoing LDN who received a multimodal analgesic regimen and a historical cohort. The multimodal cohort had a significantly shorter length of stay (LOS) (days, mean ± SD: 1.8 ± 0.7 vs. 2.6 ± 0.8; p  < .001) and a greater proportion who were discharged on postoperative day (POD) 1 (38.6% vs. 1.5%; p  < .001). The total morphine milligram equivalents (MME) that patients received during hospitalization were significantly less in the multimodal cohort on POD 0‐2. The outpatient MME prescribed through POD 60 was also significantly less in the multimodal cohort (median [IQR]; 180 [150‐188] vs. 225 [150‐300]; p  < .001). The mean patient‐reported pain score (PRPS) was significantly lower in the multimodal cohort on POD 0‐2. The maximum PRPS was significantly lower on POD 0 (mean ± SD: 7 ± 2 vs. 8 ± 1, respectively; p  = .02). This study suggests that our multimodal regimen significantly reduces LOS, PRPS, and opioid requirements and has the potential to improve the donation experience.